Analysis of Teachers’ Difficulties in Implementing the Pancasila Student Profile Strengthening Project (P5) within the Merdeka Curriculum in Primary Schools - Isnaini, Fitriah; Mardiah Astuti; Miftahul Husni; Nurlaeli, Nurlaeli; Saputra, Agra Dwi (The Future of Education Journal, 2025)
The Pancasila Student Profile Strengthening Project (P5) is a project-based co-curricular activity designed to develop students in alignment with the six dimensions of the Pancasila student profile. P5 provides students with opportunities to experience project-based learning by engaging with their surrounding environment. SD Negeri 75 Palembang is one of the schools that has implemented the Pancasila Student Profile Strengthening Project. This study aims to describe the difficulties faced by teachers in implementing the Pancasila Student Profile Strengthening Project (P5) in Grade IV at SD Negeri 75 Palembang. This research employed a qualitative method with a case study design. Data were collected through observation, interviews, and documentation. The findings indicate that Grade IV teachers at SD Negeri 75 Palembang still encounter several challenges in implementing P5, including: (1) determining appropriate project themes, (2) utilizing available facilities and infrastructure, (3) limited time allocation, and (4) designing project modules. The efforts undertaken by the school to overcome these difficulties include: (1) establishing collaborations with external partners, (2) condensing P5 implementation into one month each semester, and (3) organizing teacher learning groups as a platform for teachers experiencing challenges in implementing P5.